The Effectiveness of Campus Teaching Programs in Improving Students' Literacy and Numeration - Busyairi, Ahmad; Kusuma, Anindita SHM (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
The teaching campus is one of the programs run by the government in an effort to improve the literacy and numeracy skills of students in Indonesia. This research aims to determine the effectiveness of campus teaching programs in improving students' literacy and numeracy skills at the elementary school level. To realize this goal, experimental research was applied in this research. This research was conducted at SDN 11 Praya and SDN Tapon. The number of samples in this study was 57 students, with details of 27 students at SDN 11 Praya and 20 students at SDN Tapon. The sample in this study was taken using a simple random sampling technique. There are two instruments used in this research, namely literacy and numeracy ability test instruments. This test instrument has been prepared by the campus teaching team and is used externally in Indonesian schools. The test was carried out twice, namely at the beginning of the program (pretest) and at the end of the program (posttest). The test is carried out online using a computer and/or cellphone. The research data was then analyzed using normalized gain calculations (N-gain). Based on the results of data analysis, it was found that the Teaching Campus program was effective in increasing students' literacy and numeracy. The effectiveness of the teaching campus program in improving the literacy skills of students at SDN 11 Praya is in the medium category with an N-gain score of 0.59, while the effectiveness of the teaching campus program in improving the numeracy skills of students at SDN Tapon is in the high category with an N-gain score of 0 .78.